Pengaruh Fraud Hexagon Terhadap Kecurangan Laporan Keuangan Pada Perusahaan LQ 45 Yang Terdaftar di Bursa Efek Indonesia Periode 2016-2020 - Dinda Novarina; Dedik Nur Triyanto (Jurnal Akuntansi dan Keuangan, 2022)
Financial statement fraud is a misrepresentation and intentional concealment of facts on account values in the financial statements which results in irrelevant financial information. Fraudulent financial statements can lead to internal and external conflicts within a company that can harm decision makers. This study aims to determine the effect of the fraud hexagon which consists of pressure (external pressure), capability (change of director's), opportunity (nature of industry), rationalization (auditor's opinion), arrogance (frequent number of CEO's picture), and collusion (government projects) simultaneously or partially against fraudulent financial statements on LQ 45 index companies listed on the Indonesia Stock Exchange for the 2016-2020 period. This study uses purposive sampling technique in determining the sample in order to obtain 24 companies in the LQ 45 index listed on the Indonesia Stock Exchange. This study uses a descriptive type of research with logistic regression analysis techniques using SPSS 25 software. The results of this study indicate that pressure, capability, opportunity, rationalization, arrogance, and collusion have a simultaneous effect on financial statement fraud. The partial test results show that rationalization, arrogance have a positive effect and pressure, capability, opportunity, collusion have no effect on financial statement fraud on LQ 45 index companies listed on the Indonesia Stock Exchange for the 2016-2020 period.